Atrial fibrillation burden and subsequent heart failure events in patients with cardiac resynchronization therapy devices. (3rd April 2020) - Tanawuttiwat, Tanyanan; Lande, Jeff; Smeets, Pascal; Gerritse, Bart; Nazarian, Saman; Guallar, Eliseo; Cheng, Alan
Abstract: Background: Atrial fibrillation (AF) and heart failure (HF) often coexist but little is known on how AF burden associates with subsequent episodes of HF. Objective: The aim of this study was to quantitatively assess the short‐ and long‐term association of AF burden with subsequent episodes of HF events in patients with reduced ejection fraction. Methods: Patients with cardiac resynchronization therapy (CRT) devices with at least 90 days of device data were included in the study. Time‐dependent Cox regression with a 7‐day window was used to evaluate the association of short‐ and long‐term AF burden with subsequent HF events. Each patient with HF was matched to two control patients without an HF event based on age, gender, year of implant and CRT defibrillation capability. Results: In our cohort with 2:1 matching (N = 549), 183 patients developed HF events and 275 (50.1%) had AF over an average follow‐up of 24 ± 11 months. A 1‐hour increase in short‐term AF burden was associated with a 3% increased risk of HF events (HR, 1.034; 95% confidence interval [CI], 1.012‐1.056; P  = .01; HR for 24‐hour = 2.23). In contrast, the association between long‐term AF burden and subsequent HF events was not statistically significant (HR, 1.009; 95% CI, 0.992‐1.026; P  = .373). Conclusion: A 24‐hour increase in AF burden is associated with a more than two‐fold increased risk of HF events over the subsequent week while the long‐term AF burden is not significantly associated with HF events.